Question
upstudy study bank question image url

Use pascaf's triangle to solve \( (1-x)^{-1 / 3} \)

Ask by Elliott Bowers. in Ghana
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ (1-x)^{-1/3} = 1 - \frac{1}{3}x + \frac{2}{9}x^2 - \frac{14}{243}x^3 + \cdots \]

Solution

To solve \( (1-x)^{-1/3} \) using Pascal's triangle, we can use the binomial series expansion. The binomial series for \( (1-x)^n \) is given by: \[ (1-x)^n = \sum_{k=0}^{\infty} \binom{n}{k} (-x)^k \] where \( \binom{n}{k} \) is the binomial coefficient, defined as: \[ \binom{n}{k} = \frac{n(n-1)(n-2)\cdots(n-k+1)}{k!} \] For our case, we have \( n = -\frac{1}{3} \). Thus, we can write: \[ (1-x)^{-1/3} = \sum_{k=0}^{\infty} \binom{-\frac{1}{3}}{k} (-x)^k \] Now, we need to calculate the first few terms of this series. The binomial coefficient for negative \( n \) can be calculated as follows: \[ \binom{-\frac{1}{3}}{k} = \frac{(-\frac{1}{3})(-\frac{1}{3}-1)(-\frac{1}{3}-2)\cdots(-\frac{1}{3}-(k-1))}{k!} \] Let's calculate the first few terms of the series expansion for \( k = 0, 1, 2, 3 \): 1. For \( k = 0 \): \[ \binom{-\frac{1}{3}}{0} = 1 \] 2. For \( k = 1 \): \[ \binom{-\frac{1}{3}}{1} = -\frac{1}{3} \] 3. For \( k = 2 \): \[ \binom{-\frac{1}{3}}{2} = \frac{(-\frac{1}{3})(-\frac{4}{3})}{2!} = \frac{\frac{4}{9}}{2} = \frac{2}{9} \] 4. For \( k = 3 \): \[ \binom{-\frac{1}{3}}{3} = \frac{(-\frac{1}{3})(-\frac{4}{3})(-\frac{7}{3})}{3!} = \frac{-\frac{28}{81}}{6} = -\frac{14}{243} \] Now, substituting these values into the series expansion, we get: \[ (1-x)^{-1/3} \approx 1 - \frac{1}{3}x + \frac{2}{9}x^2 - \frac{14}{243}x^3 + \cdots \] Thus, the expansion of \( (1-x)^{-1/3} \) using Pascal's triangle (binomial series) is: \[ (1-x)^{-1/3} = 1 - \frac{1}{3}x + \frac{2}{9}x^2 - \frac{14}{243}x^3 + \cdots \] This series converges for \( |x| < 1 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve \( (1-x)^{-1/3} \) using Pascal's Triangle, we can use the Binomial Series Expansion, which allows us to express the term as an infinite series. The general form, based on the binomial theorem, is: \[ (1-x)^n = \sum_{k=0}^{\infty} \binom{n}{k} (-x)^k \] In our case, \( n = -\frac{1}{3} \). Therefore, we expand \( (1-x)^{-1/3} \): \[ (1-x)^{-1/3} = \sum_{k=0}^{\infty} \binom{-1/3}{k} (-x)^k \] The binomial coefficient \( \binom{-1/3}{k} \) can be calculated using the formula: \[ \binom{n}{k} = \frac{n(n-1)(n-2)\cdots(n-k+1)}{k!} \] Replacing \( n \) with \( -\frac{1}{3} \) gives us the coefficients needed for the series. The first few terms look like this: - For \( k=0: \quad \binom{-1/3}{0} = 1 \) - For \( k=1: \quad \binom{-1/3}{1} = -\frac{1}{3} \) - For \( k=2: \quad \binom{-1/3}{2} = \frac{(-1/3)(-4/3)}{2} = \frac{2}{9} \) - For \( k=3: \quad \binom{-1/3}{3} = \frac{(-1/3)(-4/3)(-7/3)}{6} = -\frac{28}{162} = -\frac{14}{81} \) Putting these together, we get: \[ (1-x)^{-1/3} \approx 1 + \frac{1}{3}x + \frac{2}{9}x^2 - \frac{14}{81}x^3 + \ldots \] This series converges for \( |x| < 1 \). Enjoy exploring the magic of series expansion and see how it can transform your calculations!

Related Questions

Latest Pre Calculus Questions

1.3.2 Make a conjecture with regard to \( r^{n} \) and \( S_{n} \) as \( n \rightarrow \infty \) (2) 1.4 CASE 3: \( r=1 \) 1.4.1 What is the sum of the geometric series \[ S_{n}=a+a r+a r^{2}+\ldots a r^{n-1} \text { if } r=1 ? \] 1.4.2 Make a conjecture with regard to \( r^{n} \) and \( S_{n} \) as \( n \rightarrow \infty \) 1.5 CASE 4: \( r=-1 \) 1.5.1 What is the sum of the geometric series \[ S_{n}=a+a r+a r^{2}+\ldots a r^{n-1} \text { if } r=-1 ? \] 1.5.2 Do the sums above approach some finite particular number as \( n \rightarrow \infty \) i.e. is the sequence divergent or convergent? 1.6 CASE 5: \( -1<r<1 \) REQUIREMENTS: - One A4 papers - Provided grid 1.6.1 Write THREE possible values of \( r \) such that \( -1<r<1 \). 1.6.2 Step 1. Cut the A4 size paper along the longest side into two equal Rectangles and define their areas to be 16 unit \( ^{2} \). 1.6.3 Step 2. Place one half of the rectangle in Step 1 on the desktop and cut the other half along the longest side in to two equal rectangles. 1.6.4 Step 3. Place one half of the rectangle in Step 2 on the desktop and cut the other half along the longest side into two equal rectangles. 1.6.5 Step 4. Continue with the procedures from Step 3 until you find it too difficult to fold and cut the piece of paper you are holding. 1.6.6 Step 5. The first piece of paper you placed on the desktop has an area of \( \frac{1}{2} \) the area of the A4. The second piece of paper has an area of \( \frac{1}{4} \) the area of the A4. Write the areas of the next three pieces of paper. (3) (I) 1.6.7 Explain why these areas form a geometric sequence.
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy